Effect of agro‐waste pore formers on the microstructure, hardness, and tensile properties of porous alumina ceramics. Issue 4 (6th February 2018) - Dele‐Afolabi, Temitope; Mohamed Ariff, Azmah Hanim; Mazlan, Norkhairunnisa; Sobri, Shafreeza; Calin, Recep; Zahari Nur, Ismarrubie
Abstract: This study demonstrates a simple and economically viable approach to fabricate porous alumina ceramics shaped with low‐priced natural organic pore‐forming agents (PFAs) from rice husk (RH) and sugarcane bagasse (SCB) of various weight contents using the powder metallurgy method. Experimental findings revealed that the total porosity (44‐67vol%) and average pore size (70‐178 μm) maintained a linear relationship with rising PFA inclusion. Using the diametral compression test, the mechanical response of porous alumina samples was evaluated as a function of porosity and pore geometry. From the overall mechanical strength characterization, the susceptivity of strength on porosity became well marked as the agro‐waste shaped porous ceramics exhibited hardness, tensile strength, and elastic modulus of 529.1‐26HV, 20.4‐1.5MPa and 1662‐57MPa, respectively. Moreover, the fractography of the RH and SCB graded porous alumina samples was evaluated as a function of the respective microstructural features. With a plausible tradeoff between pore interconnectivity and mechanical strength, recommended areas of application include solid oxide fuel cells (SOFCs) design, filtration, and thermal insulation systems.